(untitled) (Journal of the College of Basic Education, 2025)
The present study aims to investigate the effectiveness of an instructional program based on active listening skills in enhancing reading comprehension among first-grade middle school female students." The researchers adopted an experimental design, specifically a non-randomized control group pretest-posttest design. The research population consisted of middle, secondary, and primary public schools for girls under the Directorate General of Baghdad Karkh/Third Governorate. Al-Ikhlas Secondary School for Girls was randomly selected as the sample for the study. A total of 71 first-grade middle school students were randomly selected, with section (B) serving as the experimental group (35 students) and section (C) as the control group (36 students). One of the researchers taught the experimental group using the proposed instructional program based on active listening skills, while the control group was taught using the traditional method. The researchers controlled for the variables of linguistic ability, intelligence, and pre-reading comprehension. The researchers studied eight reading topics and texts from the Arabic language textbook for first-grade middle school students for an entire semester (2024-2025). The experiment began on Tuesday, October 1, 2024, and ended on Tuesday, December 17, 2024, lasting for an entire semester, which is the first semester of the academic year (2024-2025). The experimental group was taught according to the proposed instructional program, while the control group was taught according to the traditional method. The researchers prepared a reading comprehension test consisting of three reading passages followed by multiple-choice questions with three options, totaling 45 items, to measure the reading comprehension level of students in both groups. Using the independent samples t-test, the following results were obtained: The performance of students in the experimental group, who were taught reading material according to the proposed instructional program, significantly outperformed the performance of students in the control group, who were taught using the traditional method, in the post-reading comprehension test.